1995
DOI: 10.1136/jcp.48.3.250
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of gastric inflammation and resolution of epithelial damage one year after eradication of Helicobacter pylori.

Abstract: Aims-To investigate the effect of eradication of Helicobacter pylori infection on gastric epithelial damage and gastritis, scored according to the Sydney system. Methods-Gastritis scores and epithelial damage were assessed in gastric biopsy specimens before, and five weeks and one year after anti-H pylori therapy in 66 patients with H pylon related gastritis. Results-The mean initial levels of activity, inflammation, atrophy, intestinal metaplasia, and H pylon scores were higher in the antrum than in the corpu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
69
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(80 citation statements)
references
References 22 publications
10
69
1
Order By: Relevance
“…There was no correlation between chronic inflammation and intestinal metaplasia and glandular atrophy. This was also seen by Witteman et al [12]. Again presence of neutrophils meant a higher density of H. pylori, chronic inflammatory infiltrate, more surface epithelial damage and lymphoid follicles.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…There was no correlation between chronic inflammation and intestinal metaplasia and glandular atrophy. This was also seen by Witteman et al [12]. Again presence of neutrophils meant a higher density of H. pylori, chronic inflammatory infiltrate, more surface epithelial damage and lymphoid follicles.…”
Section: Discussionsupporting
confidence: 65%
“…Chronic inflammatory infiltrates were present in all the cases with the majority (70%) having only mild inflammation while 27% had moderate inflammation. A study done by Witteman et al [12] observed chronic infiltrate in all biopsies but the majority had moderate inflammation. In 33% of our cases, an activity was seen, which is in accordance with a study published by Misra et al [13].…”
Section: Discussionmentioning
confidence: 99%
“…H. pylori eradication dramatically improved the inflammation scores, i.e. neutrophils and mononuclear cells, but not the degree of GIM, thus confirming the findings of previous studies in which the effect of H. pylori eradication therapy led to an improvement in the severity of inflammation (Witteman et al, 1995;van der Hulst et al, 1997). However, no significant improvement in the inflammation scores was found in patients with gastric cancer (Group DYS).…”
Section: Studysupporting
confidence: 78%
“…Although there are many reports regarding the histological changes including metaplasia and dysplasia following eradication of H. pylori, the results have been conflicting (Table 1) Table 1. Summary of studies on changes of GIM scores after successful H. pylori eradication Some reported that the histologic grade of GIM had improved after eradication (Genta et al, 1993;Uemura et al, 1997;Nardone et al, 1999;Sung et al, 2000;Ohkusa et al, 2001;Kokkola et al, 2002;Correa et al, 2000;Ley et al, 2004;Mera et al, 2005;You et al, 2006) but the others did not find any change (Witteman et al, 1995;Forbes et al, 1996;van der Hulst et al, 1997;Hibi et al, 1997;Satoh et al, 1998;Tucci A et al, 1998;Tepes et al, 1999;El-Omar et al, 2000 ;Kim et al, 2000 ;Kuipers et al, 2004 ;Tanaka et al, 2006). Some of the reasons for these discrepancies may be ethnic variations, completeness of eradication of the disease and the stage of the disease when treatment is initiated and short follow-up (most studies up to 1 year) (Kokkola et al, 2002;Forbes et al, 1996;Tucci A et al, 1998;Tepes et al, 1999;Kim et al, 2000;Tanaka et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In the same way, other randomized studies identified that H. pylori eradication in intestinal metaplasia could be important in the regression of this precancerous lesion [76,[109][110][111]119,120]. Oppositely, other trials, both follow-up and randomized control, had not identified regression of intestinal metaplasia when H. pylori eradication was administrated [121][122][123][124][125][126][127][128][129].…”
Section: Discussionmentioning
confidence: 95%